Research Review on Blockchain Adaptation to VAT - Lubis, Nurul Izzah; Kesuma, Sambas Ade; Muda, Iskandar (Ridwan Institute, 2023)
Blockchain technology may provide a solution for the tax industry. It is a distributed ledger that makes it possible to trade anything of value securely, openly, and with less threat of fraud. People might find it simpler to pay their taxes, and governments might find it easier to close the tax gap. But getting from theory to practice is a long journey that also presents challenges, which needed to be discussed. This paper reviewed previous research specifically on the adaptation of blockchain to Value-Added System (VAT). Apart from the theoretical framework and proposed prototype, the majority of research used a qualitative approach, according to the findings. The decentralized network was mostly used as the blockchain structure and design for VAT, with a private block. The consensus that’s mainly used among the articles is PoA, PoA, and PBFT.